Microtensile Bond Strength of Translucent Glass Fiber Posts to Intra-radicular Dentin - N. Mohammadi; M. Abed Kahnamoui; ME. Ebrahimi Chaharom; S. Kimyai; M. Bahari (Tehran University of Medical Sciences, 2009)
Objective: The aim of the present study was to compare microtensile bond strengths (μTBS) of glass fiber posts to different parts of intra-radicular dentin using conventional method and one-shot technique under different light intensities. Materials and Methods: Twenty-eight single-rooted teeth were prepared to receive fiber posts: Group 1: Conventional method at light intensity of 600 mW/cm2; Groups 2, 3 and 4: One-shot technique at light intensities of 600, 800 and 1000 mW/cm2 respectively. Dumbbell- shaped slices were obtained from the samples and submitted to micro-tensile testing. The data were analyzed using two-way ANOVA and paired-samples t-test. Results: There were no significant differences in μTBS values of the cervical and middle thirds between the groups (P>0.05). μTBS values in the cervical thirds in groups 2 and 3 were significantly higher than those in the middle thirds (P>0.05). However, there were no such differences in groups 1 and 4 (P>0.05). Conclusion: It is proper to simultaneously cure the resin cement and the adhesive agent (one-shot technique); however, in that case, high light intensities (1000 mW/cm2) are recommended to achieve identical bond strength values in the cervical and middle thirds.